Sistem Informasi Pemasaran dan Diferensiasi Produk terhadap Keputusan Pembelian Konsumen - Juliani Juliani; Syawaluddin Syawaluddin; Aidil Putra; Thomas Sumarsan Goh (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine and analyze the effect of Marketing Information Systems and Product Differentiation on Consumer Purchase Decisions of PT. Medan Deli Kencana Palace. This research method is descriptive quantitative. The collection method with a survey approach. The total population and sample in this study were 38 people. The sampling technique used is saturated sampling technique. Data collection methods are interviews, study documentation, questionnaires and literature studies. Variables are measured using a Likert scale. The data analysis model used to answer the hypothesis is multiple linear regression analysis. The results showed, a) the marketing information system variable with a t count value (2.956) is greater than t table with a value (2.03011) and a significance value of 0.004 <0.05; b) product differentiation variable with a t count (2.849) greater than t table with a value (2.03011) and a significance value of 0.002 <0.05. In conclusion, simultaneously there is a positive and significant influence between marketing information system variables and product differentiation on consumer purchasing decisions of PT. Medan Deli Kencana Palace. Partially, there is a positive and significant influence between marketing information system variables and product differentiation on PT. Medan Deli Kencana Palace. Keywords: Product Differentiation, Consumer Purchase Decisions, Marketing Information Systems